2000
DOI: 10.1016/s1074-7613(00)80203-4
|View full text |Cite
|
Sign up to set email alerts
|

A Second Amplifier Function for the Allergy-Associated FcεRI-β Subunit

Abstract: Genetics studies have identified the gene for the high-affinity IgE receptor (FC(epsilon)RI) beta subunit as a candidate gene for atopy. We have shown that beta is an intrinsic signaling amplifier leading to enhanced allergic responses in vivo. Here we report that beta has a second amplification function: the amplification of Fc(epsilon)RI cell surface expression. This function is due to an early association of beta with alpha, resulting in improved trafficking and maturation of alpha and receptor complexes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
153
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 51 publications
6
153
0
1
Order By: Relevance
“…For example, loss of Fc⑀RI ␤ should reduce competition for the ␥ subunit (55)(56)(57)(58). Accordingly, we have observed increased Fc␥RIII expression and signaling coincidental with Fc⑀RI down-regulation (63).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, loss of Fc⑀RI ␤ should reduce competition for the ␥ subunit (55)(56)(57)(58). Accordingly, we have observed increased Fc␥RIII expression and signaling coincidental with Fc⑀RI down-regulation (63).…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly, we have observed increased Fc␥RIII expression and signaling coincidental with Fc⑀RI down-regulation (63). Kinet's laboratory convincingly showed that Fc⑀RI ␤ amplifies both the expression and signaling of the IgE receptor (55)(56)(57)(58). Given the novel role of the ␤-chain as an Fc⑀RI amplifier and the presence of ␤-chain polymorphisms in FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although a functional receptor is expressed both as a tetramer (αβγ 2 ) and a trimer (αγ 2 ) in humans [8], intracellular signals [9,10] in addition to cell-surface expression [11] have been reported to be amplified significantly by the β-chain, indicating that the β-chain increases the sensitivity of cell activation to stimulation by allergens. Therefore functional inhibition of the β-chain is a reasonable strategy to suppress allergic reaction by raising the threshold of FcεRI-mediated cell activation by decreasing both the intracellular signals and the cell-surface FcεRI expression.…”
Section: Introductionmentioning
confidence: 99%
“…8 FcεRIß forms part of the tetrameric FcεRI complex (αβγ 2 ) on mast cells and basophils, 9 and plays a central role in both enhancing surface expression of the receptor complex and amplifying the IgE-mediated signal cascade. 12,13 FcεRIß also associates with the low affinity receptor complex for IgG, FcγRIII, on mast cells, 14,15 and has been proposed as an important enhancer of allergic responses mediated through FcγRIII as well as FcεRI. 16 Based on the sequence homology of HTm 4 to CD20 and FcεRIß, together with its cellular distribution, it is likely that HTm 4 will also have a role in signal transduction as part of a multimeric receptor complex on leucocytes.…”
Section: Introductionmentioning
confidence: 99%